2006
DOI: 10.1063/1.2195111
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Curie temperatures in Fe and Co magnetic nanoparticle assembly on single-crystalline Al2O3∕NiAl(100) with normal metal capping layer

Abstract: The ferromagnetism of Fe nanoparticle assembly on Al2O3∕NiAl(100) is observed above 150K with the coverage larger than 5 ML (monolayer). Cu capping layer induces an enhancement of the Curie temperature (TC) in both Fe and Co magnetic nanoparticle assembly. The TC of Fe nanoparticle assembly with 2 and 6 ML Cu capping layer is enhanced by ∼20K and even higher, indicating the critical effects of metallic capping layer in such magnetic nanostructures as nanoparticle assembly. The capping layer effect would be cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…As showing in Fig. 1, our measurements are in agreement with previous reports [2][3][4] indicating that the Co magnetization remains to be in-plane with reduced magnetization (M s ) and coercivity upon 1 ML of Cu overlayer deposition.…”
supporting
confidence: 95%
See 1 more Smart Citation
“…As showing in Fig. 1, our measurements are in agreement with previous reports [2][3][4] indicating that the Co magnetization remains to be in-plane with reduced magnetization (M s ) and coercivity upon 1 ML of Cu overlayer deposition.…”
supporting
confidence: 95%
“…Capping non-magnetic Cu on top of the Co layer could change the Curie temperature [2,3] and the anisotropy [4] within the magnetic layer. The coercivity of Co is also sensitivity to the thickness of Cu overlayer [5,6].…”
mentioning
confidence: 99%
“…Cu-K a x-rays contribute these very large main peaks, (002) and (004), which confirm the highly oriented crystalline structure of the graphite substrate. 10,11 The other satellite peaks at approximately 12 and roughly 24.5 are Cu-Kb diffraction peaks of HOPG(002) and HOPG(004), respectively. Because the small peaks at h ¼ 18 and 20 appear in clean HOPG and all the other two patterns, they may occur because of a number of disordered graphite planes, such as HOPG (110), and are attributed to the background features of the HOPG substrate.…”
Section: Resultsmentioning
confidence: 98%
“…4(b), 4(d), and 4(f) suggesting cluster coalescence to be restricted to their basis. It has been shown that this effect leads to a slow enhancement of T C [55].…”
Section: Magnetism Of Self-assembled Fe Nanoclustersmentioning
confidence: 99%